Analysis of Factors Influencing the Decision of Couples of Reproductive Age on the Selection of Intra-Uterine Devise Contraceptive Devices - Nurfajryaty Nurfajryaty; Asriwati Asriwati; Indah Anggraini (Newinera Publisher, 2022)
Introduction In 2021 the number of PUS in the working area of the Calang Health Center is 3,037 people with 1,984 active family planning participants (65.52%) and 517 MKJP users, namely IUDs (25.97%). This shows that MKJP users, namely IUDs in the working area of the Calang Health Center work area, are still relatively low considering the number of PUS and active family planning participants is very high. This method is a combination (mixed methods research) Accidental Sampling technique 95 samples on quantitative and 9 informants on qualitative . Quantitative data were analyzed using univariate, bivariate and multivariate. Qualitative data by data reduction, presentation and drawing conclusions. Quantitative results there is no relationship between knowledge, there is a relationship between attitude, socio-culture, parity, husband's support, officer support, and there is no significant relationship between distance, facilities, to the selection of intra-uterine device devices ( IUD), Logistic regression test results Attitude OR= 1.897 Socio-cultural OR= 3.160 husband support OR= 2.804 role of health workers OR= 4.183, the role of the officer is the dominant independent variable influencing the choice of intra uterine devise contraception (IUD) with OR = 4,183. The results of the qualitative analysis show that the majority of PUS do not choose intrauterine device (IUD) contraception, due to the prevailing habits in society. It is recommended that the Health Service evaluate family planning services, it is hoped that they will provide proper and clear counseling about IUDs to PUS as the target audience.